Hermeneutics of Gender: A Comparative Study of Hermeneutical Models Amina Wadud and Farid Esack - An Najmi Fikri Ramadhan (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
The aim of this research is to compare the hermeneutical models of Amina Wadud and Farid Esack. Hermeneutics is known as a new interpretive model used by Muslim feminist scholars, to reinterpret verses of the Koran that are interpreted textually and with gender bias. This research is qualitative research with the type of library research. Then the data collected in document form was analyzed using descriptive-comparative figures against Amina Wadud's hermeneutical model. The results of the research show that there are similarities and differences between the two hermeneutics. One of the most obvious similarities is that they both belong to philosophical hermeneutics and the objectiveist cum subjectivist school. Even though there are also differences between the two, the hermeneutic offer made by Amina Wadud and Farid Esack is an attempt jihad gender in seeking justice and freeing women from the patriarchal cultural system caused by religious interpretations that are biased against women.